Comparison of Full‐Season and Double‐Crop Soybean and Grain Sorghum Systems in Central and Southeastern Virginia. (1st July 2017) - Thomason, Wade; Chim, Bee Khim; Holshouser, David; Behl, Harry; Balota, Maria; Xia, Kang; Frame, William; Black, Tyler
Abstract : Core Ideas: Grain sorghum is a viable alternative crop in the Mid‐Atlantic region. Grain sorghum can be successfully doublecropped after small grain in the Mid‐Atlantic region. Depending on commodity prices both grain sorghum and soybean can be profitable crop choices. Double‐cropping soybean [ Glycine max (L.) Merr.] after winter small‐grains is common in the mid‐Atlantic region. Grain sorghum ( Sorghum bicolor L. Moench) can also be double‐cropped after small grain and sorghum production in the region is increasing due to greater local demand for feed grains. The objective of this experiment was to evaluate and compare the yield and agronomic characteristics of grain sorghum planted full season or double‐cropped after wheat ( Triticum aestivum L.), barley ( Hordeum vulgare L.), or triticale (× Triticosecale ) with soybean in the same rotations. Four field experiments were conducted in Virginia at the Southern Piedmont Agriculture Research and Extension Center (SPAREC) (Appling sandy loam) and Tidewater Agriculture Research and Extension Center (TAREC) (Nansemond loamy sand) in 2012 to 2014. The experimental design was a split‐plot with 14 treatments and four replications. Main plot was winter crop (barley, triticale, or wheat) and the subplot either soybean or sorghum. In three of four instances, full‐season grain sorghum yields were greater than double‐crop, while this was true in half of trials for soybean. Still, double‐crop grain sorghum yields averaged over 2.9 Mg ha −1 indicating strong potential for this use in the region. Estimated net return to land and management was generally higher for soybean than sorghum except sorghum double‐crop following triticale. The highest net return was estimated for soybean double‐cropped following wheat (US$745.64 ha −1 ), and the lowest net return was sorghum following barley ($189.55 ha −1 ), due to the lower sorghum grain yield and the lower value of barley.